The molecular control of tomato fruit quality traits: the trade off between visual attributes, shelf life and nutritional value - Carneiro, RT; Lytovchenko, A; McQuinn, R; Vallarino Castro, José G.; Giovannoni, James J.; Fernie, Alisdair R; Rose, JKC; Osorio-Algar, Sonia (My University, 2013)
Tomato (Solanum lycopersicum) is an established model to study fleshy fruit development and ripening and is an important crop in terms of its economic and nutritional value. Tomato fruit quality is a function of metabolite content which is prone to physiological changes related to fruit development and ripening. It has been described some ripening tomato mutants, delayed fruit deterioration (DFD), non-ripening (NOR) and ripening-inhibitor (RIN) which substantially extend “shelf life” in tomato for up to several months when defined in terms of softening, water loss and resistance to postharvest biotic infection. However, it is not known whether this extension in “shelf life” is in fact a desirable objective from the perspective of nutritional quality of the fruits. The aim of this work was to use a metabolomics approach join to genomic tools to characterize compositional changes (sugars, amino acids, organic acids and carotenoids) of non-softening tomato mutants reported (DFD, NOR and RIN) in comparison with the normally softening fruits (Ailsa Craig and M82) during ripening and postharvest shelf-life. Important results related with ripening gene expression and metabolic evolutions are shown.
Keywords: Tomates - Aspectos nutricionales; Tomato; Fruit; Shelf life; Ripening; Nutritional value